2006
DOI: 10.1111/j.1745-6584.2006.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Effects of Multinode Wells on Solute Transport

Abstract: Long-screen wells or long open boreholes with intraborehole flow potentially provide pathways for contaminants to move from one location to another in a ground water flow system. Such wells also can perturb a flow field so that the well will not provide water samples that are representative of ground water quality a short distance away from the well. A methodology is presented to accurately and efficiently simulate solute transport in ground water systems that include wells longer than the grid spacing used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Solute can move within a long well or borehole during pumping or in the absence of pumping. Results with solute-transport simulations (Konikow and Hornberger 2006b) using this new capability have agreed with earlier work suggesting that intraborehole flow can provide a preferential pathway for vertical solute migration.…”
Section: Computer Modelingsupporting
confidence: 78%
See 1 more Smart Citation
“…Solute can move within a long well or borehole during pumping or in the absence of pumping. Results with solute-transport simulations (Konikow and Hornberger 2006b) using this new capability have agreed with earlier work suggesting that intraborehole flow can provide a preferential pathway for vertical solute migration.…”
Section: Computer Modelingsupporting
confidence: 78%
“…Intraborehole flow has been recognized in previous studies (Gass et al 1977;Reilly et al 1989;Lacombe et al 1995;Church and Granato 1996;Konikow and Hornberger 2006b) as a mechanism for rapidly transporting contaminants Fig. 7 Groundwater ages on the vertical plane of hydrologic symmetry a 2 years after the introduction of a nonpumping multi-node well, at which time a pumping well was introduced; and age after pumping for an additional b 2 years and c 6 years in the subsurface.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations showed a monitor well forming a connection between the higher and lower hydraulic head zones (Elci and others, 2001;Elci and others, 2003). Konikow and Hornberger (2006) modeled preferential groundwater flow through monitor wells and concluded that solutes can be redistributed in different aquifers through monitor wells. Zinn and Konikow (2007) used a numerical model to demonstrate that borehole flow can substantially bias groundwater ages determined from water samples, but they also indicated that the effects are highly dependent on local or regional flow conditions and may change with time.…”
Section: Previous Investigationsmentioning
confidence: 99%
“…Future code development may include transport in surface-water networks represented by the SurfaceWater Routing (SWR) Package for MODFLOW (Hughes and others, 2012). Though not included in this release of MT3D-USGS, future efforts may extend the generalized network capabilities to intra-borehole transport problems (Konikow and Hornberger, 2006;Neville and Tonkin, 2004;Neville and Zhang, 2010). This could be implemented by applying the generalized network solution to the linear network of well nodes (that is, well bores that effectively connect multiple model nodes, as in the case of long well screens that span multiple model layers).…”
Section: Solute Transport Through Generalized Networkmentioning
confidence: 99%